MicroRNA‐3191 promotes migration and invasion by downregulating TGFBR2 in colorectal cancer. Issue 6 (15th February 2019) - He, Hongjuan; Zhao, Xiaojuan; Zhu, Ziqing; Du, Le; Chen, Erfei; Liu, Shuzhen; Li, Qiqi; Dong, Jing; Yang, Jin; Lei, Lei
Abstract: Mutations in transforming growth factor beta receptor II (TGFBR2) are detected in up to 30% of overall colorectal cancer (CRC). Dysregulation of some microRNAs participated in the CRC pathogenesis. In this study, we used the gene ontology analyses, the Kyoto Encyclopedia of Genes and Genomes pathway analyses and gene set enrichment analysis to indicate that miR‐3191 was involved in the regulation of transforming growth factor beta (TGF‐BETA) signal pathway in CRC. These bioinformatics results were supported by data obtained from CRC samples and experiments in vitro. The luciferase reporter assay was used to confirm that miR‐3191 modulates TGF‐BETA signal pathway by targeting TGFBR2. By transwell migration and invasion assays, we showed that miR‐3191 promoted CRC cell migration and invasion by downregulating TGFBR2. And it may serve as a novel therapeutic strategy for treating CRC patients.